Investigating the impact of synonymous gene recoding on a recombinantly expressed monoclonal antibody under different process parameters - Nayiri M. Kaissarian; Stephanie L. Sandefur; Arnab Ghosh; Upendra K. Katneni; Wendy Walton; Christopher C. Frye; Anton A. Komar; Chava Kimchi‐Sarfaty (Bioengineering & Translational Medicine)
Abstract Monoclonal antibodies (mAbs) are commonly used biologic therapeutics with a wide variety of clinical applications. During the development process, manufacturers consider different production parameters to improve protein yield and achieve appropriate quality of the product. Synonymous gene recoding is one of such attributes that is often considered and implemented to enhance protein expression. However, it has to be used with caution, as it may lead to protein misfolding and ER stress, which complicates efforts to manufacture the desired mAb. To investigate how changing mRNA sequence composition under different protein production parameters might affect the quality of recombinantly produced mAbs, we performed a comprehensive and systematic study assessing impact of synonymous gene recoding (commonly referred to as codon optimization) strategies in the context of varied cell culture parameters on product quality, biochemical and functional characteristics. We report the impact of these parameters on mAb glycosylation profiles, charge variant profile, aggregation, fragmentation, and mAb functional response from combinations of different production parameters. These results uncovered a complex interplay of sequence composition and manufacturing parameters and emphasize the importance of assessing changes to key quality attributes when optimizing mAb manufacturing, including the use of synonymous gene recoding.